INFRARED MULTIPLE-PHOTON DISSOCIATION AS A SOURCE OF REACTIVE FREE-RADICALS - METHYLENE REVISITED - Ashfold, M; Fullstone, M; Hancock, G; Ketley, G (Società Italiana di Fisica, 1981)
Rate constants for collisional removal of ã1 A 1 CH2 and CD2 have been directly measured for the first time, by using IR multiplephoton dissociation to produce the radicals and time-resolved laser-induced fluorescence to detect them. Contributions to the removal processes from both intersystem crossing and chemical reaction are discussed. © 1981 Società Italiana di Fisica.